Smart Room Control and Monitoring System Based on Internet of Things - Andika, Bayu; Candra, Oriza (Journal of Industrial Automation and Electrical Engineering, 2024)
In this modern era, the development of Internet of Things technology has opened up opportunities to create a smarter home environment that is easily accessible from anywhere. This research aims to create and develop a smart room system that utilises the Blynk platform and Google Assistant to efficiently control and monitor devices in the room. This system allows users to control electronic devices such as lights, fans, and other household appliances through the Blynk application, manual switches and provides voice-based control capabilities using Google Assistant. This system is designed using NodeMCU Esp8266 microcontroller as the main controller, which is connected to sensors and equipment that are controlled in this tool to monitor and control room conditions. The Blynk app is used as the user interface for real-time control, while integration with Google Assistant allows control via voice commands. Tests of the system that have been carried out both using Blynk, manual switches and Google Assistant show that the device can respond to commands quickly and provide accurate feedback on the status of the device and room conditions. With this system, users can improve comfort and energy efficiency in their homes, as well as enjoy the convenience of controlling devices through various media, both mobile applications and voice commands. The system also provides opportunities for further future development of an integrated smart room ecosystem